The Antecedents of Intention to Stay among Millenials: Work Engagement as Mediator - Saraswati, Kiky Dwi Hapsari; Lie, Daniel; Lie, David Sugianto; Winduwati, Septia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Study on millenial generation is essential to conduct since in the near future the millenials will dominate the workforce and hold strategic positions in industry. According to references, millenials are well-known for their reluctance to stay working in one place for a long-time period. Many speculations have arisen to explain the issue, whether it is caused by their positive as well as the negative characteristics. This study aimed to investigate the factors affecting millenial’s intention to stay. Three levels of context were involved as researched variables, namely work passion, quality of work life, and work engagement as mediator. Quantitative and non-experimental study was applied to test the hypotheses. Using convenience sampling technique, 125 millenial workers in Jakarta, Indonesia, were recruited and completed the online questionnaires. The questionnaires to measure the researched variables are Intention to Stay Scale, Work Passion Scale, Quality of Work Life Scale, and Utrecht Work Engagement Scale (UWES). Regression analysis reported that intention to stay was significantly affected by work passion and quality of work life. Moreover, work engagement was also proven to be a significant mediator that bridged the association between intention to stay and both of independent variables, namely work passion and quality of work life.